Absent. The English Teacher : The English Teacher - Gurira, Danai; Afolayan, Jide Olugbenga, 1971-; McCreery, Kathleen; Moyo, Mirirai, 1979-; Salter, Nikkole; Kilalea, Rory (Book collections on Project MUSE., 2009)
Theatre and drama are very much part of our every day lives. These four plays: Belonging by Mirirai Moyo, When I Meet my Mother by Kathleen McCreery, In the Continuum by Danai Gurira and Nikkole Salter, and Power Failure by Jide Afoylan reveal the dynamism and variety of theatre. They also reveal that from Zimbabwe to Brazil, Nigeria to the USA, societies despite their diversity share many common problems and challenges. Annotated for schools with questions and notes by Rory Kilalea, teachers and students will find this a richly accessible text.